Effects on Career Development From Sharing One's Story: Young Professionals' Experiences With Family Planning Voices. Issue 3 (May 2020) - Ballard Sara, Anne; Futrell, Elizabeth; Gurman, Tilly
Supporting the development of young family planning professionals is key to fostering communities of practitioners that can help countries achieve family planning goals. The Family Planning Voices (FP Voices) storytelling initiative, created by The Knowledge for Health Project and Family Planning 2020, documents stories from people around the world who are passionate about family planning. This qualitative evaluation used in-depth interviews ( n = 11) with young professionals (ages 18-30) to uncover the effects of sharing their story with FP Voices. Participants came from 10 countries in one of three regions, Latin America ( n = 2), South Asia ( n = 2), and Africa ( n = 7). Findings highlight that sharing one's story with FP Voices served as a professional development opportunity and instilled confidence and pride among young professionals. Additionally, participants linked access to a professional headshot and the experience of participating in an interview to their professional development. Participants often discussed the recognition they gained from sharing their story and the resulting increase in professional connections and opportunities. Participants hoped that their stories would inspire and encourage others and support recognition of the value of young professionals to the larger family planning field. In sum, storytelling initiatives like FP Voices can motivate and create community and opportunity among young professionals.